Кремневые сырьевые стратегии Большого Донбасса в эпоху камня – палеометалла - Колесник, А.В. (Археологический альманах, 2009)
This article is devoted to the study of flint supplying strategies during Stone Age and Paleometal Age in Donbas region. Donetsk mountain ridge or Donbas is the large geological formation in the southern part of the East European Plain. Owing to the peculiarities of its geological history the region abounds of Upper Cretaceous deposits with good quality flint. The Stone Age and Halcolithic flint workshops have long been known in the region. The regional flint exploitation is based on the number of variants of the flint supplying strategies. The specific Donbass type of evolution of the flint supplying strategies is under discussion in the essay.